The Influence of Brand Image, Satisfaction, and Brand Trust on Brand Loyalty Fore Coffee in Yogyakarta - Saputra, Bagas Tegar; Ariani, Dorothea Wahyu (Research Horizon, 2024)
This research aims to analyze the influence of Brand Image, Satisfaction, and Brand Trust on Brand Loyalty Fore Coffee in Yogyakarta. The sample in this study was 130 respondents who had purchased Fore Coffee at least once in Yogyakarta. The data collection method in this research uses a method with measurement tools in the form of questionnaires. The instrument test results stated that the data in this study was proven to be valid and reliable. The classical assumption test states that the data in this study are normally distributed and the regression model is free from heteroscedasticity and multicollinearity. The results of this research can be concluded that Brand Image has a positive and significant effect on Brand Loyalty. Satisfaction has a positive and significant effect on Brand Loyalty. Brand Trust has a negative effect on Loyalty and Coffee Brand. These results have implications for future researchers to study the factors that form brand loyalty. The findings of this research have implications for managers to pay attention to factors that can increase consumer trust in brands and other factors that influence brand loyalty.